2006
DOI: 10.1021/bi0514515
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Activity and Structural Differences of Amphipathic Peptides Derived from Trialysin,

Abstract: Trialysin is a pore-forming protein found in the saliva of Triatoma infestans (Hemiptera, Reduviidae), the insect vector of Chagas' disease. The protein is active against a broad range of cell types from bacteria to eukaryotic cells. Recognizing that the N-terminus of trialysin harbors the lytic motif [Amino, R., Martins, R. M., Procopio, J., Hirata, I. Y., Juliano, M. A., and Schenkman, S. (2002) J. Biol. Chem. 277, 6207-6213], we designed a set of peptides scanning this region to investigate the structural b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…3.5.2 Coding for proteins found only in triatomines: 3.5.2.1 Trialysin: We identified two contigs that matched the protein trialysin, a pore-forming molecule present in the (SG)s of T. infestans Martins et al, 2006) (Fig. 9).…”
Section: Similarity To Bacterially Induced Peptide Hdd1 (From Hyphantmentioning
confidence: 99%
See 1 more Smart Citation
“…3.5.2 Coding for proteins found only in triatomines: 3.5.2.1 Trialysin: We identified two contigs that matched the protein trialysin, a pore-forming molecule present in the (SG)s of T. infestans Martins et al, 2006) (Fig. 9).…”
Section: Similarity To Bacterially Induced Peptide Hdd1 (From Hyphantmentioning
confidence: 99%
“…Studies in which synthetic peptides containing portions of the Nterminus of trialysin have been tested for their lytic properties against the infective stage of T. cruzi, Escherichia coli and human erythrocytes revealed differences in specificity and activity for the tested targets. The cell membrane is the main target of antimicrobial peptides, thus the diverse lipid composition and distribution or the presence of other components in the cell membrane of the various organisms play an important role in the modulation of peptide/ membrane interaction, leading to the differentiation of their action Martins et al, 2006).…”
Section: Similarity To Bacterially Induced Peptide Hdd1 (From Hyphantmentioning
confidence: 99%
“…We identified six contigs (assembled from 54 ESTs that matched the protein named trialysin from T. infestans 77,78 ) having between 38% and 88% identity at the aa level with their best match in the NR database, all from T. infestans. Trialysin, which belongs to a multigene family, is a pore-forming molecule present in the SGs of T. infestans.…”
mentioning
confidence: 99%
“…The structural features of the protein and charge distribution, as well as the composition of the target membrane, are important determinants for protein/membrane interaction and lysis specificity. 77,78 Antigen 5 family. This family of secreted proteins belongs to the CAP family (cysteine-rich secretory proteins; Ag5 proteins of insects; pathogenesis-related protein 1 of plants).…”
mentioning
confidence: 99%
“…In parallel, we studied the lytic activity of several synthetic peptides corresponding to the Nterminus of trialysin (Martins et al 2006). We found that although all peptides folded into α-helices in the presence of SDS or trifluoroethanol (TFE), only the ones close to the N-terminus of mature trialysin were lytic to T. cruzi, E. coli, and erythrocytes.…”
Section: Structure and Function Of Triatoma Infestans Proteinsmentioning
confidence: 99%